THE INFLUENCE OF BRAND IMAGE, TRUST, AND SERVICE QUALITY ON REVISIT INTENTION MEDIATED BY PATIENT SATISFACTION (CASE STUDY AT THE BHAYANGKARA HOSPITAL OF THE YOGYAKARTA SPECIAL REGION REGIONAL POLICE) - Ahmad Syakur Banafif; Kosasih; Rulia; Etty Sofia Mariati Asnar; Farida Yuliaty; Vip Paramarta (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of Brand Image, trust, and service quality on patients’ revisit intention with patient satisfaction as a mediating variable at Bhayangkara Hospital, POLDA of the Special Region of Yogyakarta. The increasing competition among hospitals demands a comprehensive evaluation of the factors that shape patient loyalty. This research uses a quantitative approach with a survey method involving 250 patient respondents selected through purposive sampling. Data analysis was conducted using Partial Least Square (PLS) with SmartPLS 4 software. The findings show that Brand Image, trust, and service quality have a positive and significant effect on patient satisfaction and revisit intention. Patient satisfaction is also proven to mediate the relationship between the three independent variables and revisit intention, as indicated by p-values below 0.05. These results confirm that a positive hospital image, trust in the competence of medical staff, and superior service quality create a satisfying patient experience, thus encouraging revisit behavior. Theoretically, this study strengthens the conceptual model that satisfaction is a key element bridging patients’ perceptions and loyalty in the healthcare sector. Practically, the findings provide implications for hospital management to enhance the synergy between image management, trust-building, and service quality improvement to create sustainable patient satisfaction and retention.